Path Dependency and Future Adaptation of Coastal Cities: Examples From the Asia-Pacific - Nunn, Patrick D.; Smith, Timothy F.; Elrick-Barr, Carmen (Frontiers in Environmental Science, 2021)
The need for Asia-Pacific coastal cities to adapt effectively and sustainably to accelerating (relative) sea-level rise is growing. If such adaptation does not occur in a timely manner, then it could result in socio-economic problems that will reverberate throughout the region. Using examples of coastal Asia-Pacific cities that are characterised by differing geographical settings and cultural contexts, this study argues that the main barrier to such adaptation is path dependency. In this sense, path dependency is a legacy of past decisions that have been influenced by topography, economic goals, and the cultural-political characteristics of key decision-making groups. These path dependencies manifest as various adaptation preferences, which to date have been dominated by hard engineering solutions. In an era of accelerating climate change there is now a need to seek alternatives to in-situ urban growth. This paper argues that an understanding of a city’s path dependency is key to optimizing the effectiveness of future adaptation.